2018
DOI: 10.1007/s11695-018-3165-4
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption in Obese Patients Before and After Gastric Bypass as Assessed with the Alcohol Marker Phosphatidylethanol (PEth)

Abstract: Introduction Roux-en-Y gastric bypass (RYGB) causes more rapid and enhanced absorption of alcohol. RYGB patients have also been reported to use more inpatient care for alcohol-related disease than do patients after other bariatric procedures. The present study was designed to evaluate alcohol consumption level before and after gastric bypass using a sensitive and specific alcohol biomarker. Materials and Methods Two separate consecutive groups of patients and a group of healthy blood donors, as reference group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…PEth has become well accepted as a direct biomarker of alcohol consumption (Aradottir et al, 2006; Beck et al, 2018; Simon, 2018; Varga et al, 1998; Walther et al, 2018) for the following reasons: First, PEth is highly specific because, as mentioned above, it is only generated in the presence of ethanol, and therefore is a direct biomarker of alcohol intake. Second, PEth is highly sensitive because it is detectable after consuming alcohol equivalent to just one or two standard drinks (Javors et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…PEth has become well accepted as a direct biomarker of alcohol consumption (Aradottir et al, 2006; Beck et al, 2018; Simon, 2018; Varga et al, 1998; Walther et al, 2018) for the following reasons: First, PEth is highly specific because, as mentioned above, it is only generated in the presence of ethanol, and therefore is a direct biomarker of alcohol intake. Second, PEth is highly sensitive because it is detectable after consuming alcohol equivalent to just one or two standard drinks (Javors et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Walter et al reported a prevalence of alcohol consumption (PEth > 0.05 μmol) of 26% 2 years after surgery among RYGB patients, which is in agreement with the alcohol consumption in our study (26.1%). In their study, a group of healthy blood donors was used as the reference, with PEth results > 0.05 μmol found in 44% of the controls, indicating that there could be higher alcohol consumption in the general population than among bariatric surgery patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the PEth levels of the bariatric surgery groups were lower than those of the reference group at baseline and postoperatively; notably, in both bariatric surgery groups, the PEth levels increased significantly postoperatively compared to baseline but did not reach the PEth levels of the control group. However, this study included only PEth ≥ 0.05 μmol/L without classifying it further as 0.05–0.30 μmol/L or > 0.30 μmol/L; in addition, the prevalence of alcohol overconsumption and risk factors were not examined [ 14 ]. The aim of this study was to evaluate the prevalence of alcohol overconsumption at 1 and 2 years after bariatric surgery and to identify possible risk factors associated with alcohol overconsumption.…”
Section: Introductionmentioning
confidence: 99%
“…Using validated questionnaires may be more helpful than serum markers of alcohol consumption ( e.g. , phosphatidylethanol), which may vary unpredictably in patients with a history of bariatric surgery[ 64 ].…”
Section: Future Directions: Clinical Care For Aud After Bariatric Sur...mentioning
confidence: 99%